Behaviour of geotextile reinforced soil retaining wall - Chandrasekaran, B. (2009)
Small scale model tests and finite element analyses were carried out to study the behaviour of Geotextile Reinforced Soil (GRS) retaining walls. The behaviour of GRS walls as affected by the length, the spacing and the stiffness of the reinforcement and by the stiffness of the wall facing has been investigated.